Long-distance bus services in Europe: Concessions or free market? - Didier van de Velde (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This paper makes a review of the current situation in the interurban passenger transport market by coach in Europe, describing for a number of selected countries the regulatory setting, the main market actors, the main developments have taken place in the last decade or two and a number of resulting challenges, especially in terms of regulation. The paper starts with a chapter on country cases. The next chapter summarises the main facts and trends that appear out of this review. The last chapter draws a few conclusions.
Keywords: 330